SLE initially presenting with neuropsychiatric manifestations and seizure, case report - Abdulrahman Ali M. Khormi; Faisal Taher Hijazi (Immunity, Inflammation and Disease)
Abstract Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder exhibiting variable disease courses and multiple clinical manifestations. SLE's aetiology remains unclear; however, different environmental (e.g., ultraviolet light, infections, drugs, etc.), genetic, and hormonal factors are potentially involved. A positive family history and history of having other autoimmune illnesses are considered high‐risk factors for SLE; nevertheless, most SLE cases are scattered. The 2019 European League Against Rheumatism/American College of Rheumatology classification criteria for SLE include at least one positive antinuclear antibody test as a mandatory entry criterion, followed by additive weighted standards grouped in seven clinical (constitutional, haematological, neuropsychiatric, serosal, musculoskeletal, renal, and mucocutaneous) and three immunological (antiphospholipid antibodies, complement proteins, and SLE‐specific antibodies) domains weighted from 2 to 10, with patients accumulating ≥10 points being diagnosed with SLE. Herein, we report a case of neuropsychiatric lupus, a rare and severe form of SLE.